THE POSITION OF FOREIGN NATIONALS IN LAW REVIEW APPLICATIONS AT THE CONSTITUTIONAL COURT OF THE REPUBLIC OF INDONESIA - Aulia Sukrunnisa; Deno Orie Nurandari; Darma; Muh. Alfath Dasri (Jurnal Al Tasyri'iyyah, 2024)
ABSTRACT This The constitutional court as one of the judicial power institutions authorized to carry out testing of laws against the 1945 constitution (judicial review), both formally and materially. In practice, not all parties can become applicants in the Judicial review in the Constitutional Court. One of the requirements to become an applicant in this case is an individual Indonesian citizen who feels his rights are violated by the issuance of a regulation by executive bodies. However, it does not rule out the possibility that foreign nationals can also experience acts of human rights violations during their stay in Indonesia. The issue of the position of foreign citizens in judicial review at the Constitutional Court is an interesting study because it concerns a person's constitutional rights. The research method used is Library research. The type of research used is normative juridical. As for the results of this study, the author finds the fact that foreign citizens do not have the right or position as an applicant in a judicial review at the Constitutional Court. This is because there is no legal basis that regulates the position of foreign citizens in testing the Law against the 1945 Constitution in the Constitutional Court. Therefore, the Constitutional Court is not authorized to accept and examine cases of judicial review of laws filed by foreign nationals. Keywords: Legal Standing, Foreign Citizens, Constitutional Court.